The role of co-spray-drying procedure on the preformulation of intranasal propranolol hydrochloride - Ambrus, Rita (Acta chimica slovenica, 2014)
The use of dry powder formulations presents an alternative through which to achieve better deposition and residence time in the nasal cavity, increased stability and possible absorption enhancement. The most important factors involved in the preformulation are particle size and physical stability. Propranolol hydrochloride a model drug was subjected to spray-drying technology to form an intranasal dry powder. Particle size reduction of the drug was carried out by integration (spray-drying) methods, using different excipients. The micrometric properties were characterized by size and morphology. The structure was determined through the use of differential scanning calorimetry, X-ray powder diffraction and Fourier transform infrared spectroscopy investigations. It was concluded that the intranasal dry powder formulation of propranolol hydrochloride can be achieved with a suitable particle size without polymorph modification or chemical decomposition.
Keywords: diferenčna dinamična kalorimetrija; intranasal powder formulation; micronization; pray-drying; predformulacijske študije; propranolol hidroklorid; propranolol hydrochloride; slv; stabilnost učinkovin; structural analysis